Spatial–temporal distribution characteristics of Harpadon nehereus in the Yangtze River Estuary and its relationship with environmental factors - Li, Yu; Gao, Chunxia; Chen, Jinhui; Wang, Qing; Zhao, Jing (Frontiers in Marine Science, 2024)
To investigate the spatial–temporal distribution characteristics of Harpadon nehereus in the Yangtze River Estuary (YRE) and its relationship with environmental factors, this study used the data from resource and environmental surveys conducted in the YRE and adjacent waters during August (summer) and November (autumn), 2017–2022. Generalized additive models (GAM) were employed to analyze the relationships between the relative resources of H. nehereus and environmental factors and to predict the spatial–temporal distribution of H. nehereus resources in 2022. Our results revealed that the best model deviance explained in summer and autumn was 64.89% and 49.90%, with average effect sizes of 0.75 and 0.70, respectively, for cross-validated regression slopes. Water temperature and salinity were identified as the key environmental factors influencing the relative resources of H. nehereus in the YRE. Overall, there were notable seasonal differences in the relationship between the relative resources of H. nehereus and environmental factors. The relative resources of H. nehereus in the YRE were higher in the summer than in autumn. In summer, both water temperature and salinity exhibited multi-wave nonlinear relationships with the relative resources of H. nehereus, while in autumn, the relative resources of H. nehereus showed a positive linear relationship with water temperature and a non-linear relationship with salinity. Additionally, the predicted and observed values of the relative resources of H. nehereus in 2022 showed similar spatial distribution patterns. The relative resources of H. nehereus was higher in the northern branch than in the southern branch and the offshore regions compared to the near-estuary regions. Altogether, our study provides a scientific basis for conservation management and sustainable utilization of H. nehereus resources in the YRE, thereby contributing to the restoration and management of fishery resources in the region.